(untitled) (Medico Legal Update, 2021)
Background and Aims: Physical abuse is the most critical problem in Mosul city children and the extent of physical abuse is currently unknown. Aim of this study to determine the prevalence of physical abuse among sample of Mosul schoolchildren, aged 12–18 years. Material and Method: A cross-sectional study was carried out from 1st, December 2018 to 4th March 2019. The settings chosen by multicultural sampling with a systematic sampling technique of 800 child (396 male and 404 female) using a self-reported questionnaire. Result: A total of 800 intermediate school children, age group 14-15 years represent 43.6%, male to female ratio 1:1, 36.1% of these had experienced physical abuse and 32.6% abused by mothers. The relationship between the parent educations and father’s job shows high significant rate 0.000, 0.004. Conclusion: physical abuse Mosul city had high prevalent in comparison with others. Psychological and physical problems of children were the main predictors.